Architected Tungsten Carbide Electrodes Using Origami Techniques. Issue 12 (26th September 2019) - Islam, Monsur; Keck, Devin; Martinez-Duarte, Rodrigo
Abstract : The fabrication of 3D complex shapes of porous tungsten carbide (WC) using an origami‐inspired manufacturing technology is presented. This is the first report of this technology for the fabrication of complex WC structures with density as low as 0.06 g cm −3 . The porous WC origami structures are fabricated by heat treatment of folded paper infiltrated with an aqueous solution of ammonium metatungstate (AMT). WC purity up to 96% is achieved when using an AMT concentration of 20%, synthesis temperature of 1300 °C, and heating rate of 2.5 °C min −1 . The as‐synthesized WC features a Brunauer–Emmett–Teller (BET) surface area of 102.06 m 2 g −1 . Beyond obtaining high‐purity WC, the focus is on understanding the effect of the microstructure on the mechanical performance of origami structures. Increasing the purity of WC decreases the elastic modulus and compressive strength of the origami structure, which is attributed to the increasing grain size of the crystalline phase materials and increase of graphitic phases in carbon with increasing temperature. Furthermore, the WC origami structures exhibit good and stable electrical conductivity under compressive stress. These initial results encourage further work on using paper as a scaffold to fabricate origami‐inspired multifunctional structures, for structural energy components. Abstract : Architected tungsten carbide (WC) electrodes are fabricated using origami and heat treatment techniques. Different process parameters are studied for the synthesis of WC structures from a cellulosic precursor. The WC origami structures exhibit good mechanical properties with a low structural density. Furthermore, these WC structures exhibit excellent electrical stability under compressive load, which is highly desirable for architected electrode material.